Developing and evaluating complex interventions: updating Medical Research Council guidance to take account of new methodological and theoretical approaches. (November 2018) - Skivington, Kathryn; Matthews, Lynsay; Craig, Peter; Simpson, Sharon; Moore, Laurence
Abstract: Background: Medical Research Council (MRC) guidance on developing and evaluating complex interventions was first published in 2000 and updated in 2006. The two core guidance documents continue to be very highly cited but, given the interest in and extent of methodological development, there is a strong case for a more current version. We aimed to update the guidance to take account of developments in methods and practice, with an emphasis on identifying relevant methods used in a wider range of disciplines and sectors than the traditional core focus on randomised trials. Methods: A series of events and processes have been undertaken to progress this work, overseen by a scientific advisory group: consultation workshops at relevant UK health conferences to gain input on key issues for update in the new guidance; a scoping literature review and gap analysis to identify critical appraisal of the previous guidance and publications that provide detail on theoretical and methodological developments in key areas for update; and an expert workshop, held in London in May, 2018, with 39 leading researchers in the field. Key issues and debates are being thematically analysed and will be used to draft the guidance document, which will then be presented at relevant conference workshops for further input from researchers in the field. Findings: Although a work in progress, several key themes have been identified (eg, the application of complex systems science, research priority-setting, the use of programme theory, and natural experiment opportunity). Additionally, the expert workshop called for the guidance to be more inclusive, and to move away from experimental methods as the best or only option. Interpretation: The new core guidance document will be produced in 2019. In addition to including several new and updated sections, it will be more relevant to the evaluation of non-researcher led interventions, such as policy changes; and it will be framed from the starting point of problem identification rather than choice of research method. Funding: MRC and National Institute for Health Research (MR/N015843/1).